Tamansiswa and The Ethics of Non-Punitive Discipline: Reframing Punishment in Progressive Education - Miftakhuddin, M; Saud, Udin Syaefudin; Riyadi, Arie Rakhmat (Universitas Muhammadiyah Surakarta, 2025)
This article reconceptualizes Tamansiswa's among system as a theory-bearing model of non-punitive discipline that contributes to global progressive education. Drawing on a qualitative multiple-case study of two Tamansiswa primary schools, the article reanalyses empirical data from the author's master's thesis using ethics of care and critical pedagogy as complementary lenses. Findings demonstrate that Tamansiswa's rejection of punishment is philosophically grounded in respect for the child's kodrat alam and the cultivation of budi pekerti; that teachers as pamong exercise ethical authority through sustained relational presence, moral exemplarity, and individualized guidance; that discipline is reframed from obedience to moral autonomy and self-regulation via dialogical reflection and communal norms; and that among operates as a Southern Theory, offering a decolonial alternative to punitive, Eurocentric disciplinary paradigms. The analysis shows how care-based practices and anti-oppressive pedagogies cohere to produce agency and communal responsibility without coercion, and how indigenous ethical vocabularies can inform restorative and autonomy-supportive frameworks. Practical implications include reorienting teacher education toward relational competencies, embedding ethical frameworks within restorative policies, and recognizing local wisdom as a curricular resource. The study's bounded case design and reliance on secondary analysis limit claims of generalisability; future research should pursue comparative, longitudinal, and mixed-methods studies to evaluate scalability and outcomes. By foregrounding Tamansiswa as both a historical praxis and a contemporary, normative resource, the article advances an ethical and ideological reframing of punishment with theoretical and practical relevance for educators and policymakers globally. The findings invite policymakers to integrate culturally grounded ethics into national disciplinary frameworks urgently.